Effect of bias voltage on microstructure and properties of magnetron sputtering TaN coating. Issue 4 (May 2019) - Yubao, Zhang; Zhigang, Li; Jinfeng, Li; Nan, Zhang; Hongtao, Zhao
Abstract: A series of TaN films were coated on Al2 O3 at various bias voltages by magnetron sputtering technique. Effect of bias voltage on the microstructure, roughness, deposition rate, binding force of coating-substrate, electrical properties of the TaN coating were investigated by X-ray diffraction (XRD), atomic force microscope (AFM), profile meter, scratch tester and four points probe respectively. The results suggest that the TaN coating were formed by face-center δ-TaN crystals and the preferential orientation of the coatings varied with the bias voltage; the deposition rate and the binding force of coating-substrate reached maximum value of 5.71nm/min and 4.5N when the bias voltage was 80 V, the roughness and the square resistance reached the minimum value of 0.509nm and 15.58Ω/□